PENDAMPINGAN PEMBELAJARAN BAHASA INGGRIS PADA GURU TK DHARMA WANITA 1 SUMBERJO GONDANG NGANJUK - Muhammad Lukman Syafii; Azid Syukroni; Ayok Ariyanto (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Introducing English from an early age should be supported by adequate facilities and infrastructure. The teacher as a component of the learning process manager needs to understand the framework of early childhood thinking (AUD) so that learning management can be carried out properly. The problem that arises is that the kindergarten teachers complain that there is no syllabus for learning English in kindergarten, while learning English in kindergarten must be implemented as early as possible. This service aims to develop and apply an English learning syllabus in Kindergarten (TK). The method applied in this service is a workshop and the application of the workshop. The partner for this dedication is the Kindergarten Principal. The result of this dedication is the completion of the syllabus for learning English for Kindergarten and will apply it in further learning in the classroom. Some activities such as singing and telling stories can be included in the category of presentations and explanations, or games. Transition songs are used to accompany the change from one activity to the next. At that time, it was hoped that students could play while learning because the world of children is a world of play and they are also happy when they are invited to sing, of course, with material inserted.